Element abundance and the physics of solar energetic particles - Reames, Donald V. (Frontiers in Astronomy and Space Sciences, 2024)
Acceleration and transport of solar energetic particles (SEPs) causes their abundances, measured at constant velocity, to be enhanced or suppressed as a function of each ion's magnetic rigidity, and hence it's atomic mass-to-charge ratio A/Q. Ion charges, in turn, depend upon source electron temperature. In small "impulsive" SEP events, arising from solar jets, acceleration during magnetic reconnection causes steep power-law abundance enhancements. These impulsive SEP events can have 1000-fold enhancements of heavy elements from sources at ~2.5 MK, and similar enhancements of 3 He/ 4 He and of streaming electrons that drive type-III radio bursts. Gamma-ray lines show that solar flares also accelerate 3 He-rich ions but their electrons and ions remain trapped on magnetic loops so they dissipate their energy as X-rays, γ-rays, heat, and light. "Gradual" SEPs accelerated at shock waves, driven by fast coronal mass ejections (CMEs), can show powerlaw abundance enhancements or depressions, even with seed ions from the ambient solar corona. In addition, shocks can reaccelerate seed particles from residual impulsive SEPs with their pre-existing signature heavyion enhancements. Different patterns of abundance often show that heavy elements are dominated by a different source from that of H and He. Nevertheless, the SEP abundances averaged over many large events define the abundances of the corona itself, which is found to differ from the solar photosphere as a function of the first ionization potential (FIP) since ions, with FIP < 10 eV, are driven upward by forces of electromagnetic waves which neutral atoms, with FIP >10 eV, cannot feel. Thus, SEPs provide a measurement of element abundances in the solar corona, distinct from the solar wind, and may even better define the photosphere for some elements.